COMPUTIONAL FLUID DYNAMICS (CFD) APPLICATION FOR DUCTED PROPELLER - Celik, Fahri; Guner, Mesut (YILDIZ TECHNICAL UNIV, 2005)
There have been many developments in propeller design since 1800, but the geometry and operation of the propeller were not changed considerably. However, many new propulsion systems by adding energy saving devices to propeller have been developed during this time. One of which, called duct, is widely used at heavily loaded conditions for higher propulsive efficiency. A review on duct and finite volume method for hydrodynamic analysis of ducted propeller will be given in this study. The analysis will be carried out in variation of ship speeds. The results will be compared with those of lifting surface method.
Keywords: Duct; Propeller; Lifting surface; Finite volume; Auxiliary propulsion systems; Engineering